Art of Tattooing: Medical Applications, Complications, Ethical and Legal Aspects - Barwa, J; Rani, A; Singh, R (International Journal of Medical Toxicology and Forensic Medicine, 2016)
The art of tattooing has been practiced since the ancient times for a variety of reasons. The descriptive, decorative patterns have not only been used as a means of identification but have established itself in the field of medicine as well, being employed as a therapeutic modality or diagnostic method. These include corneal tattooing, gastrointestinal tattooing during endoscopy, reconstructive and cosmetic tattooing for camouflage, radiotherapy field marking etc. An emerging application of tattooing is medical alert tattooing often practiced by the patients themselves without medical consultation inscribing their disease condition or allergy to a particular medication which may affect diagnosis or treatment. However, tattoos indicating advance health directives (do not resuscitate/do not defibrillate) or the organ donor tattoo pose ethical and legal problems as they may not reflect patient’s current wishes. Furthermore, they are not recognized as meeting any of the legal requirements, so they cannot be considered as valid directives or as consent, but only as a way to guide treatment decisions. In this paper, we outline a brief review of the numerous applications, its advantages, potential drawbacks along with the ethical and legal issues related to it.